express y=(x-2)^(2)+4 in standard form
a. y=x^(2)-4x+4 b. y=x^(2)-4x+8 c. y=x^(2)-4x d. y=x^(2)+4x+4
a. y=x^(2)-4x+4 b. y=x^(2)-4x+8 c. y=x^(2)-4x d. y=x^(2)+4x+4
a. x=-6 b. x=6 c. x=-4 d. x=4
a. one real root b. two real roots c. two imaginary roots c. cannot be determined
a. -20 b. 28 c. 24 d. -22
a. 5 b. 2x^(2) c. -3 d. -3x
a. vertex b. x-intercepts c. y-intercepts d. none of the above
a. (4,41) b. (2, 33) c. (-4,9) d. (-2, 1)
2y=4x+2 y+3=2x
, given constraints x-ygreater than or equal to -2 x+y greater than or equal to -4 and 2x-y less than or equal to 4